Bifacial PV Systems at High Latitude: Modeling and Validation with Monitoring Data - Huerta Hugo; Ranta Samuli; Wang Shuo; Heinonen Aleksi; Jouttijärvi Sami; Driesse Anton; Miettunen Kati (Germany, 2025)
In this paper, we model and evaluate the performance of two different Bifacial Photovoltaic implementations at high latitude locations with latitudes close to 60° N, consisting of a set of seaside PV canopies with 100 kWp power and a roof-mounted PV system with 140 kWp power. The modelling is done by using the backward ray-tracing technique in combination with detailed 3D models to achieve a more accurate evaluation of the rear-side irradiance and energy yield prediction. An improved irradiance sampling method was developed to simulate an accurate irradiance map on each cell of the modules with high-speed asynchronous execution. The detailed irradiance power output of the canopy system was simulated over one year and compared with monitored data for an analysis of energy gain and loss. Results show that 7% of the total energy comes from the rear irradiance, in which 1% of the total energy is from the enhancement of snow. However, snow coverage on the front side could cause a loss of 2.8% of the total energy, which indicates that an appropriate snow clean-up measure might be important to further optimize the yield of PV systems in high latitude regions. The methodology was implemented preliminarily for the second configuration, roof-mounted PV to prove its replicability. Preliminary results show only 2% of the energy is produced by the rear side. The modelling methodology was proven to be reliable and useful when evaluating different bifacial PV configurations.
Proceedings of the 40th European Photovoltaic Solar Energy Conference and Exhibition in Lisbon, Portugal